Choice of cell-delivery route for skeletal myoblast transplantation for treating post-infarction chronic heart failure in rat. - Satsuki Fukushima; Steven R Coppen; Joon Lee; Kenichi Yamahara; Leanne E Felkin; Cesare M N Terracciano; Paul J R Barton; Magdi H Yacoub; Ken Suzuki (PLoS ONE)
Background Intramyocardial injection of skeletal myoblasts (SMB) has been shown to be a promising strategy for treating post-infarction chronic heart failure. However, insufficient therapeutic benefit and occurrence of ventricular arrhythmias are concerns. We hypothesised that the use of a retrograde intracoronary route for SMB-delivery might favourably alter the behaviour of the grafted SMB, consequently modulating the therapeutic effects and arrhythmogenicity. Methods and results Three weeks after coronary artery ligation in female wild-type rats, 5x10(6) GFP-expressing SMB or PBS only (control) were injected via either the intramyocardial or retrograde intracoronary routes. Injection of SMB via either route similarly improved cardiac performance and physical activity, associated with reduced cardiomyocyte-hypertrophy and fibrosis. Grafted SMB via either route were only present in low numbers in the myocardium, analysed by real-time PCR for the Y-chromosome specific gene, Sry. Cardiomyogenic differentiation of grafted SMB was extremely rare. Continuous ECG monitoring by telemetry revealed that only intramyocardial injection of SMB produced spontaneous ventricular tachycardia up to 14 days, associated with local myocardial heterogeneity generated by clusters of injected SMB and accumulated inflammatory cells. A small number of ventricular premature contractions with latent ventricular tachycardia were detected in the late-phase of SMB injection regardless of the injection-route. Conclusion Retrograde intracoronary injection of SMB provided significant therapeutic benefits with attenuated early-phase arrhythmogenicity in treating ischaemic cardiomyopathy, indicating the promising utility of this route for SMB-delivery. Late-phase arrhythmogenicity remains a concern, regardless of the delivery route.